(untitled) (IAHS Medical Journal, 2025)
Background: Hospital Acquired Infections (HAIs) are posing an imminent threat to patient safety as well as the general well-being of healthcare personnel on a worldwide scale. The World Health Organization (WHO) estimates that at any given time, around 1.4 million people suffer from infectious complications because of HAI. One of the most common healthcare associated infections is Catheter Associated Urinary Tract Infection (CAUTI). This current study was aimed to identify base line CAUTI rate and risk factors responsible for it. Materials and methods: A longitudinal study was conducted from July 2022 to June 2023 in the Department of Microbiology, Chittagong Medical College. The current study brought attention to highlight the rate of CAUTI in the Chittagong Medical College Hospital. The data were analyzed by using SPSS version 27 and the results were summarized by using tables and graphs. The protocol was approved by the Committee of the research cell and ethical clearance was taken from the Ethical Review Committee (ERC) of Chittagong Medical College. Results: 330 catheterized urine sample were collected for research purpose from clinically suspected CAUTI. 52.42% were confirmed CAUTI. Current study showed most of the CAUTI patients were female (69.09%) and from Obstetrics and Gynaecology ward (45.66%) with a CAUTI rate 8.12 per thousand catheter days. Whereas overall CAUTI rate was 7.39 per thousand catheter days. Current study shows type 2 diabetes mellitus was the most common comorbidities associated with CAUTI cases (39.88%). Conclusions: The study’s findings provide valuable insights into the rate and risk factors associated with CAUTIs IAHS Medical Journal Vol 7(2), December 2024; 93-99